IDENTIFIKASI MORFOLOGI DAN KEKERABATAN SALAK DI JAWA TIMUR - Christie, Chitra; Agus Lestari , Nia (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
Salak has the scientific name Salacca zalacca including a low-growing family of palms. This seasonal fruit plant is a type of horticulture that has the potentioal to become an axport commodity in Indonesia. In East Java, especially in Lumajang, Madura and Kediri are areas that produce salak commodities. Morphological identification aims to obtain basic traits so that the appearance or phenotype of each accession can be distinguished quickly and easily, by estimating how much genetic diversity it has. This study aims to determine the morphological characters and to determine the salak kinship of Lumajang, Kediri and Madura. The result of phylogeny analysis of the Salacca zalacca kinship in East Java show that the results of the kinship analysis of the salak in the Lumajang, Kediri and Madura areas formed 2 large groups or cluster. So it can be concluded that the Salacca zalacca originating from the Lumajang, Kediri and Madura areas still come from the same ancestor. This can be seen from the value of kinship distance, the morphological identificaion equation. In addition, environmental factors can also affect the morphology of plants. Sunlight intensity, N and P nutrients can also affect the difference in leaf color